Optimal nitrogen fertilization timing and rate in dry-seeded rice in Northwest India - Mahajan, G.; Chauhan, B.S.; Gill, M.S. (Wiley, 2011)
Dry‐seeded aerobic rice (Oryza sativa L.) (DSR) is an emerging production system in the northwest Indo‐Gangetic Plains (IGP) due to increasing constraints of labor and water availability. Very limited research has been done in this region on optimizing nutrient management to produce high yield in DSR. In this study, we investigated yield and dry matter of rice, and N translocation in response to timing and rate of N application. Nitrogen was applied in three splits (as per regional recommendation of transplanted rice) and four splits with or without N application at sowing time (basal dose) at rates of 120, 150, and 180 kg ha−1. The crop did not respond to increasing N levels from 120 to 180 kg ha−1 when applied in three splits. However, increasing N application to 150 kg ha−1 when applied in four splits with no N at sowing time resulted in 7.55 and 7.76 Mg ha−1 yields in 2009 and 2010, respectively; highest among all the treatments. Application of 150 kg N ha−1 in four splits with no‐N at sowing resulted in 9 to 12, 19 to 24, and 5% increase in panicle number m−2, filled grains panicle−1, and 1000‐grain weight, respectively, over the application of 120 kg N ha−1 in three split doses. The relative contribution of mean preanthesis assimilates to grain increased from 23% at 120 kg N ha−1 applied in three splits to 40% at 150 kg N ha−1 applied in four splits with no N at sowing, indicating that fertilizer application schedules for transplanted rice are not suitable for DSR. This study revealed that application of N at anthesis may further boost the productivity of DSR. From these results, it could also be inferred that, for DSR, application of N at sowing time can be skipped because it may not be immediately used by the emerging seedlings.